Correlation between isothermal crystallization properties and slow crack growth resistance of polyethylene pipe materials. (December 2019) - Gholami, Farzad; Pircheraghi, Gholamreza; Rashedi, Reza; Sepahi, Abdulhanan
Abstract: In this study, three PE100 polyethylene materials with fairly different short chain branch distributions were used to characterize the relation between thermal properties and creep test failure time. The samples were thermally characterized using isothermal and non-isothermal differential scanning calorimetry (DSC). The three resins showed different behavior after fitting on the Avrami equation. N-100J2 sample, in which short chain branches (SCBs) are located on longer molecule chains, has a lower chain mobility and higher crystallization time, while N-100J1 has the opposite crystallization properties. Also, these samples had different Avrami index, n . Microstructural evaluation of these samples revealed that the Avrami index had a direct relationship with the morphology of samples and the higher n correlates to formation of more spherulite structures. The creep test result showed that the sample with a lower crystallization rate and lower Avrami index was more resistant against slow crack growth (SCG) because of its crystalline morphology with the obstacles in crack growth. There is a meaningful relationship between lamellae arrangement and failure time; when a crystalline segment in resin has more spherulite structures, higher Avrami index, the boundary of these spherulites may act as weak regions in front of crack and consequently lead to easier crack growth in such material. Highlights: There is a direct relationship between the location of SCBs and the performance of resin against slow crack growth. The comonomers make crystals thinner and increase the number of tie molecules and chain entanglements in the amorphous phase. The randomly distributed lamellar morphology decreases the chance of the crack to find a preferential path for growth. With increasing  n  (the Avrami index), the resistance to slow crack growth in polyethylene resins is reduced significantly.